(untitled) (Annals of Medical Research, 2021)
Aim: Fatty liver is a common liver disease in the community. Mitochondrial dysfunction and oxidative process cause insulin resistance, causing fatty liver. Fatty liver diseases are higher in patients infected with chronic hepatitis B virus (HBV) than the normal population. We aimed to investigate the relationship between hepatosteatosis and biochemical and histopathological parameters in chronic HBV patients. Materials and Methods: Patients with follow-up between September/2017-November/2019 with chronic HBV diagnosis were included. Demographic and histopathological data of all patients were documented. Comorbid diseases, medications and previous operations were questioned. The presence of steatosis was determined by ultrasonography (USG) to all patients. Biochemical and histopathological data were compared with the presence of steatosis. Results: A total of 94 patients, 50(53.1%) women were included in the study. As a result of liver biopsy; while 20(21.2%) patients had no fibrosis (steage 0), 74(78.8%) patients had fibrosis (steage 1-3). In USG, 45(47.8%) patients were found to have hepatosteatosis and 49(52.2%) patients were not. In the comparison between the groups; there was no significant relationship between sex, age, liver function tests, HBV-DNA level, hepatic activity index and hepatosteatosis (p>0.05). A significant relation was found between the presence of fibrosis and hepatosteatosis (p=0.021). Conclusions: Chronic HBV is an inflammatory process that ends with cirrhosis and hepatocellular carcinoma, and in this process, fatty liver may increase disease and cause disease progression. In this context, it is important to prevent the development of steatosis in chronic HBV patients. However, this should be supported in prospective studies in larger populations.